THE INFLUENCE OF CURRENT RATIO, DEBT TO EQUITY RATIO, AND RETURN ON ASSETS ON FIRM VALUE IN THE ENERGY SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2019-2023 PERIOD - Martha Ng; Steven Darwinson (Procuratio : Jurnal Ilmiah Manajemen, 2025)
The purpose of this study is to analyze the effect of the Current Ratio (CR) , Debt to Equity Ratio (DER), and Return on Assets (ROA) on firm value in the energy sector listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. This research employs a quantitative approach with purposive sampling to determine the research sample, resulting in 30 companies out of a total of 87 energy sector companies meeting the criteria. The data used are secondary data in the form of annual financial statements processed using multiple linear regression analysis. The results of the study indicate that: (1) The Current Ratio (CR) has a negative and insignificant effect on firm value; (2) The Debt to Equity Ratio (DER) has a positive and insignificant effect on firm value; and (3) The Return on Assets (ROA) has a positive and insignificant effect on firm value. Tujuan penelitian ini adalah untuk menganalisis pengaruh Current Ratio (CR) , Debt to Equity Ratio (DER), dan Return on Assets (ROA) terhadap nilai perusahaan pada sektor energi yang terdaftar di Bursa Efek Indonesia (BEI) periode 2019-2023. Penelitian ini menggunakan pendekatan kuantitatif dengan metode purposive sampling untuk menentukan sampel penelitian, sehingga diperoleh 30 perusahaan dari total 87 perusahaan sektor energi yang memenuhi kriteria. Data yang digunakan adalah data sekunder berupa laporan keuangan tahunan yang diolah menggunakan metode regresi linier berganda. Hasil penelitian menunjukkan bahwa: (1) Current Ratio (CR) memiliki pengaruh negatif dan tidak signifikan terhadap nilai perusahaan; (2) Debt to Equity Ratio (DER) memiliki pengaruh positif dan tidak signifikan terhadap nilai perusahaan; dan (3) Return on Assets (ROA) memiliki pengaruh positif dan tidak signifikan terhadap nilai perusahaan.